2023
DOI: 10.1002/adsu.202200414
|View full text |Cite
|
Sign up to set email alerts
|

Plant Protein Amyloid Fibrils for Multifunctional Sustainable Materials

Abstract: Artificial functional materials based on amyloid fibrils are proven to be a promising strategy toward functional materials. However, scaling‐up applications present sustainability concerns, as animal proteins are the main sources for fabricating amyloid fibrils. Plant‐protein‐based amyloid fibrils, a more sustainable alternative to animal proteins, are attracting increasing interests as building blocks in functional materials. Herein, 11 different sources from a wide range of plants are evaluated, and a compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…To better understand the interaction between the AFs and aminosilane, transmission electron microscopy (TEM) was employed to observe the nanofilaments suspended in water before and after amine modification. The morphology of the three AFs varied, with BLG and lysozyme forming long and straight fibrils, while black bean protein formed short and curly fibrils (Figure S1a, c and e), consistent with previous reports on the morphology characterization of these three classes of protein fibrils [14] . Since silanol groups generated after aminosilane hydrolysis can easily self‐condensate and react with surface hydroxyl groups of the support scaffold, it was observed that BLG and lysozyme fibrils (0.1 wt%) were coated by silica nanoparticles (Figure S1b, d, and Figure S2 and S3).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…To better understand the interaction between the AFs and aminosilane, transmission electron microscopy (TEM) was employed to observe the nanofilaments suspended in water before and after amine modification. The morphology of the three AFs varied, with BLG and lysozyme forming long and straight fibrils, while black bean protein formed short and curly fibrils (Figure S1a, c and e), consistent with previous reports on the morphology characterization of these three classes of protein fibrils [14] . Since silanol groups generated after aminosilane hydrolysis can easily self‐condensate and react with surface hydroxyl groups of the support scaffold, it was observed that BLG and lysozyme fibrils (0.1 wt%) were coated by silica nanoparticles (Figure S1b, d, and Figure S2 and S3).…”
Section: Resultssupporting
confidence: 91%
“…Preparation of amyloid fibrils β-lactoglobulin from whey protein isolate and black bean protein were purified according to our previous protocol. [13][14] Lysozyme from chicken egg white was purchased from Sigma-Aldrich. βlactoglobulin amyloid fibrils were prepared by incubation of 2 wt% protein solution at pH 2 and 90 °C for 6 h with magnetic stirring of 300 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations